Large-scale continuous hydrothermal production and activation of ZIF-8 - Munn, A.S.; Dunne, Peter W.; Tang, S.V.Y.; Lester, Edward (Royal Society of Chemistry, 2015)
A new method for the large-scale hydrothermal production and activation of ZIF-8 is presented in this communication. Activated ZIF-8 has been produced, at lab-scale and pilot-scale, at a rate of 27 g h-1 and 810 g h-1 respectively with the activated material showing a surface area of 1800 m2 g-1.